9514 1404 393
y-4 = -2(x+1)
The point-slope equation of a line is ...
y -k = m(x -h) . . . . . line with slope m through point (h, k)
You have m = -2 and (h, k) = (-1, 4). Putting these numbers into the above form gives ...
y -4 = -2(x +1)
using equation 2, we would make y the subject of the formula as it would be easier
This would now be called our equation 3
Now the next step is to substitute equation 3 in equation 1
Divide both sides by 27
Substitute the value of x in equation 2
you add 1 to 1 and that gives you 2